Upconversion Lasers: Stable and Low‐Threshold Optical Gain in CdSe/CdS Quantum Dots: An All‐Colloidal Frequency Up‐Converted Laser (Adv. Mater. 17/2015). (May 2015) - Guzelturk, Burak; Kelestemur, Yusuf; Gungor, Kivanc; Yeltik, Aydan; Akgul, Mehmet Zafer; Wang, Yue; Chen, Rui; Dang, Cuong; Sun, Handong; Demir, Hilmi Volkan
<x xml:space="preserve">Abstract</x> An all‐colloidal vertical‐cavity surface‐emitting laser (VCSEL) is reported by C. Dang, H. Sun, H. V. Demir and co‐workers on page 2741, which offers high performance and stability while being fully solution processed. This all‐colloidal laser is based on a stacked architecture of dielectric mirrors, based on metal oxide nanoparticles sandwiching semiconductor nanocrystals as the optical gain medium, forming an all‐solution‐processed VCSEL structure. Here, using tailored core‐shell quantum dots that have suppressed non‐radiative Auger recombination enables the achievement of sub‐mJ cm−2 frequency up‐converted lasing thresholds, which make these all‐colloidal devices highly promising for optoelectronic and biomedical applications.